168k views
2 votes
Question 4Rewrite in simplest radical formShow each step of your process.26

Question 4Rewrite in simplest radical formShow each step of your process.26-example-1
User P Jones
by
5.2k points

1 Answer

5 votes

The question is given to be:


\frac{x^{(5)/(6)}}{x^{(1)/(6)}}

Recall the exponent rule given to be:


(a^m)/(a^n)=a^(m-n)

Therefore, we can simplify the expression to be:


\frac{x^{(5)/(6)}}{x^{(1)/(6)}}=x^{(5)/(6)-(1)/(6)}

Simplifying the exponent, we have:


x^{(5)/(6)-(1)/(6)}=x^{(4)/(6)}=x^{(2)/(3)}

To write in radical form, apply the rule given to be:


a^{(m)/(m)}=(\sqrt[n]{a}^{})^m

Therefore, the answer becomes:


\Rightarrow(\sqrt[3]{x})^2

ANSWER


\frac{x^{(5)/(6)}}{x^{(1)/(6)}}=(\sqrt[3]{x})^2

User Mmd
by
5.4k points